Microfungi on Leaves of Licuala bidentata (Arecaceae) from Sarawak, Malaysia - Lateef, Adebola; Muid, Sepiah; Bolhassan, Mohamad Hasnul (Makara Journal of Science, 2015)
A microfungal survey was carried out on the living leaves and litters of Licuala bidentata in Kubah National Park in Sarawak, Malaysia. A total of 400 leaf segments (200 segments for each leaf type) were plated on two isolation media (water agar and malt extract agar) for endophytic and saprophytic fungal isolation. Forty-three microfungal species were obtained from both leaf types, 31 species identified from living leaves and 18 species from litters. Only six species were common to both leaf types, with 25 and 12 species exclusively identified from living leaves and litters, respectively. New records of fungi from this host plant and for the genus Licuala include Isthmotricladia laeensis, Chloridium sp., Mucor sp., Oidiodendron sp., Kinochaeta sp., Cryptophiale sp., Chrysosporium merdarium and Circinotrichum fertile. This study constitutes the first report on microfungal community on L. bidentata. Implications of this new report in comparison with the microfungal species on other plant species in the genus Licuala are discussed.